2016
DOI: 10.1111/joor.12415
|View full text |Cite
|
Sign up to set email alerts
|

Turned versus anodised dental implants: a meta‐analysis

Abstract: Summary The aim of this meta‐analysis was to test the null hypothesis of no difference in the implant failure rates, marginal bone loss (MBL)and post‐operative infection for patients being rehabilitated by turned versus anodised‐surface implants, against the alternative hypothesis of a difference. An electronic search without time or language restrictions was undertaken in November 2015. Eligibility criteria included clinical human studies, either randomised or not. Thirty‐eight publications were included. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 66 publications
2
19
0
5
Order By: Relevance
“…[46] Independent researchers published similar observations on other moderately rough surfaces, too. [47] Our results also show that after one year, when osseointegration has already taken place, the difference between the two surfaces diminish and the significance of the difference between implant failures disappear. Additionally, a histological study, using small sample size, also confirmed that, in the long term, both implant types maintained a decent level of osseointegration.…”
Section: Discussionsupporting
confidence: 67%
“…[46] Independent researchers published similar observations on other moderately rough surfaces, too. [47] Our results also show that after one year, when osseointegration has already taken place, the difference between the two surfaces diminish and the significance of the difference between implant failures disappear. Additionally, a histological study, using small sample size, also confirmed that, in the long term, both implant types maintained a decent level of osseointegration.…”
Section: Discussionsupporting
confidence: 67%
“…When no statistically significant heterogeneity was found, the analysis was performed using a fixed-effects model. 14,15 The risk ratio values were considered significant at P less than .05. A software program (Reviewer Manager 5; Cochrane Group) was used for the meta-analysis and to elaborate the funnel plots.…”
Section: Discussionmentioning
confidence: 99%
“…When it comes to dental implants, these were in the early years mainly manufactured with a turned (machined) surface or with an extremely highly roughened surface. The adoption of a moderately rough surface improved the survival rates . The implant abutment connection was another part of the implants that had modifications over time.…”
Section: Introductionmentioning
confidence: 99%
“…The adoption of a moderately rough surface improved the survival rates. 7 The implant abutment connection was another part of the implants that had modifications over time. The external hexagon abutment connection was originally used on the Brånemark implant, but presented some drawbacks.…”
mentioning
confidence: 99%